The Effect of Grief Expression on Instagram on Users' Digital Empathy and Emotional Response - Grisel, Ray Olwin (PELNUS | Pen en Light for Natural Union of Science, 2025)
This study explores how grief is expressed and empathized with on Instagram, focusing on the dynamics of digital mourning and emotional contagion within visual storytelling. As social media becomes a prominent platform for public and personal expressions of loss, understanding the emotional interactions that arise from such content is critical. Employing a mixed-methods approach including content analysis of grief-related Instagram posts and interviews with active users the research investigates how users respond emotionally to visual and textual expressions of mourning. The findings reveal that posts incorporating photos or videos tend to elicit stronger empathic engagement than text-only posts, with users who frequently interact with grief-related content demonstrating higher levels of digital empathy. The study also highlights the role of online mourning communities in providing emotional support and fostering shared healing experiences. These insights contribute to the growing discourse on digital empathy, affective communication, and the evolving rituals of grief in online spaces, offering implications for platform design, mental health support, and cultural understandings of mourning in the digital age.